Legal Protection for Minority Shareholders Against Share Dilution in a Private Company - Ariani Mandala Puteri (Global Legal Review, 2026)
The loss of shareholders' rights to obtain a preemptive offer on newly issued shares results in share dilution for the company's shareholders. The logical consequence of this becomes increasingly complex when the diluted shares fall below 10%, as it weakens their position in the General Meeting of Shareholders (GMS) and results in the loss of the right to file a derivative lawsuit or submit a petition for the examination of the company to the District Court in the event that the company suffers losses. The purpose of this research is to analyze the legal protection of minority shareholders against share dilution in Private Companies and the ideal legal regulation concerning the protection of minority shareholders against share dilution in Private Companies. This study employs a normative legal research method. The research findings indicate that the implementation of legal protection that can be undertaken includes, first, that minority shareholders have the right to sell their shares if they do not agree with corporate actions that are detrimental to shareholders within the scope of amendments to the articles of association; and second, the right to file a lawsuit against the company on the grounds of having been treated unfairly. The ideal legal arrangement in this regard is a legal reformulation, which includes the repeal of Article 43 paragraph (3) of the Company Law, so that the preemptive right remains attached to every shareholder in the event of the issuance of new shares. In addition, reformulation of Article 97 paragraph (6) and Article 138 paragraph (3) letter a of the Company Law is also proposed, in the form of eliminating the minimum 10% share ownership requirement related to the right to file a derivative lawsuit and a petition for a company examination to the District Court.